Madrasah Diniah as Media Teaching and Learning Islamic Moderation Values at Qur’an Learning Centers - Nur Zaytun Hasanah; Shafira Dhaisani Sutra; Sutta Wira Admojo; M Nurul Ikhsan Saleh (Edukasi: Jurnal Pendidikan, 2022)
AbstractMadrasah diniah has an essential role in educating the younger generation concerning instilling Islamic values from an early age. Moderation Islam (wasathiyah Islam) has now become a school of Islamic thought that has become a discourse. This research aimed to interpret madrasah diniah education as a medium for teaching and learning Islamic moderation values to students of Taman Pendidikan Al-Quran (Qur’an Learning Center). The research method used qualitative. This research was conducted at Baiturrahman Mosque, Sleman, Yogyakarta. The subjects were three Qur’an Learning Center teachers of the Baiturrahman Mosque. This research used data collection techniques through interviews, observations, and secondary sources. The data analysis technique used in the form of content analysis techniques. Based on the results of the research, it was found that early madrasah diniah education can be used as a medium of teaching and learning to instill Islamic moderation values.  AbstrakMadrasah diniah memiliki peran penting dalam mendidik generasi muda dalam kaitannya menanamkan nilai-nilai Islam sejak dini. Moderasi Islam (wasathiyah Islam) telah menjadi aliran pemikiran Islam yang menjadi pembicaraan. Tujuan penelitian adalah untuk menginterpretasikan pendidikan madrasah diniah sebagai media pengajaran dan pembelajaran nilai-nilai moderasi Islam pada santri Taman Pendidikan Al-Quran. Metode penelitian yang digunakan adalah metode kualitatif. Penelitian dilakukan di Masjid Baiturrahman, Sleman, Yogyakarta. Subjek penelitian adalah tiga guru santri Taman Pendidikan Al-Quran Masjid Baiturrahman. Penelitian menggunakan teknik pengumpulan data melalui wawancara, observasi, dan sumber sekunder. Teknik analisis data yang digunakan berupa teknik analisis konten. Berdasarkan hasil penelitian, ditemukan bahwa pendidikan madrasah diniah dapat dijadikan sebagai media pengajaran dan pembelajaran dalam menanamkan nilai-nilai moderasi Islam.